Compensatory Growth in Juveniles of Freshwater Redclaw Crayfish Cherax quadricarinatus Reared at Three Different Temperatures: Hyperphagia and Food Efficiency as Primary Mechanisms - Stumpf, Liane (2015)
Feeding restriction, as a trigger for compensatory growth, might be considered an alternative viable strategy for minimizing waste as well as production costs. The study assessed whether juvenile redclaw crayfish Cherax quadricarinatus (initial weight 0.99 ±0.03 g) was able to compensate for feeding restriction at different temperatures (23±1, 27±1 and 31 ±1°C). Hyperphagia, food utilization efficiency, energetic reserves, and hepatopancreas structure were analyzed. Three temperatures and two feeding regimes (DF-daily fed throughout the experiment and CF- 4 days food deprivation followed by 4 days of feeding, intermittently) were tested. The restriction period was from day 1 to 45, and the recovery period was from day 45 to 90. The previously restricted crayfish held at 23, 27, and 31 ± 1°C displayed complete body weight catch-up through compensatory growth following the restriction period with depressed growth. The mechanisms that might explain this response were higher feed intake (hyperphagia), and increased food utilization efficiency. Hepatopancreatic lipids were used as a metabolic fuel and hepatosomatic index was reduced in the previously restricted crayfish, but recovery at the same level of unrestricted crayfish occurred after the shift to daily feeding. The highest temperature affected adversely growth, feed intake, food efficiency, and metabolism of crayfish, whereas the lowest temperature and feeding restriction induced a more efficient growth of the crayfish.